External Conditions Affecting the Validity of a Legal Act - Kareem Faiz Adnan, Researcher. Ali; Abdul Qadeer Maroof , Prof.Dr. Hussein (Basra studies journal, 2025)
External conditions affecting a legal act are among the issues that sometimes limit the validity of the act, while at other times they may serve as a basis for the enforceability of certain obligations. These conditions do not form part of the act itself but relate to external matters. Moreover, these conditions may be personal, relating to the parties involved in the legal act and closely connected to them. They can be relied upon in some acts to enforce certain obligations, prevent their waiver, or expand the scope of some provisions. Other conditions are material in nature and do not pertain to the parties themselves, but rather to material circumstances, such as prior dealings between the parties, the surrounding conditions of the act, and the interest that establishes a right for one of the parties or third parties. This study details these issues and conditions throughout the research, including the introduction and conclusion.